Evolution of Neutralization Response in HIV-1 Subtype C-Infected Individuals Exhibiting Broad Cross-Clade Neutralization of HIV-1 Strains - Cheedarla, Narayanaiah; Hemalatha, Babu; Anangi, Brahmaiah; Muthuramalingam, Kannan; Selvachithiram, Murugesan; Sathyamurthi, Pattabiraman; Kailasam, Nandagopal; Varadarajan, Raghavan; Swaminathan, Soumya; Tripathy, Srikanth Prasad; Vaniambadi, S. Kalyanaraman; Vadakkupattu, D. Ramanathan; et al. (Frontiers in Immunology, 2018)
Strain-specific neutralizing antibodies develop in all Human Immunodeficiency Virus type 1 (HIV-1) infected individuals. However, only 10-30% of infected individuals produce broadly neutralizing antibodies (bNAbs). Identification and characterization of these bNAbs and understanding their evolution dynamics are critical for obtaining useful clues for the development of an effective HIV vaccine. Very recently, we published a study in which we identified 12 HIV-1 subtype C infected individuals from India whose plasma showed potent and broad cross-clade neutralization (BCN) ability [36]. In the present study, we report our findings on the evolution of host bNAb response over a period of 4 years in a subset of these individuals. Three of the 5 individuals (NAB033, NAB059 and NAB065) demonstrated a significant increase (p<0.05) in potency. Interestingly, two of the three samples also showed a significant increase in CD4 binding site specific antibody response, maintained stable CD4+ T cell counts (>350 cells/mm3) and continued to remain ART-naïve for more than 10 years after initial diagnosis, implying a strong clinical correlation with the development and evolution of broadly neutralizing antibody response against HIV-1.